Effects of beam oscillation modes on microstructure and mechanical properties of laser welded 2060 Al-Li alloy joints. (December 2021) - Zhou, Xiaohui; Zhao, Hongyun; Liu, Fuyun; Yang, Biao; Xu, Bingxiao; Chen, Bo; Tan, Caiwang
Highlights: Laser welding of 2060Al-Li alloy under different beam oscillation modes were performed. Surface collapse was reduced by the beam oscillation. Oscillated laser beam refined the grains by the enhanced fluid flow. The refined grains contributed to the improvement of microhardness value. The maximum tensile strength was obtained by '8′ shaped laser beam oscillation. Abstract: In the present work, laser welding of 2-mm-thick 2060 Al-Li alloy was performed under different beam oscillation modes. Weld seam morphology, microstructure, mechanical properties were compared. The results indicated that joints welded by oscillated laser beam possessed improved collapse, refined grains, higher microhardness and tensile strength. In fusion zone, nondendritic equiaxed grains, parallel dendrite grains and cellular dendrite grains were formed in all welded joints. After applying laser beam oscillation, the collapse decreased from 0.54 mm to 0.1 mm. The maximum tensile strength of welded joint was obtained in the case of '8′ shaped laser beam oscillation reaching 338.15 MPa, which was improved by 68% compared with that of joint without oscillation (200.58 MPa). In this case, grain characters and molten pool fluid were studied to reveal the enhancement mechanism of beam oscillation . Enhanced fluid velocity produced with '8′ shaped laser oscillation refined grains and more high angle grain boundaries (HAGBs) were formed. The grain size was reduced from 105.27 μm to 89.67 μm in cellular dendrite zone (CDZ). The percentage of HAGBs increased from 65.2% to 75.2%. The refined grains resulted in larger and more uniform microhardness value and better mechanical behavior. Shallower, crystal-sugar shaped dimples were formed in fracture surface obtained by pure laser welding without oscillation while deeper and bigger dimple, including equiaxed dimple and conical dimple were generated in the fracture surfaces of oscillated laser welded joints.